Prophylaxis escalation in severe von Willebrand disease: a prospective study from the von Willebrand Disease Prophylaxis Network. (14th July 2015) - Abshire, T.; Cox‐Gill, J.; Kempton, C. L.; Leebeek, F. W. G.; Carcao, M.; Kouides, P.; Donfield, S.; Berntorp, E.
Summary Background Treatment of mucosal bleeding (epistaxis, gastrointestinal bleeding, and menorrhagia) and joint bleeding remains problematic in clinically severe von Willebrand disease (VWD). Patients are often unresponsive to treatment (e.g. desmopressin or antifibrinolytic therapy) and may require von Willebrand factor (VWF) replacement therapy. There are little data on the use of prophylaxis in VWD, and none have been applied in a prospective, treatment escalation design. Objective Evaluate the effect of escalating dose prophylaxis in severe VWD. Methods Patients eligible for enrollment in this prospective study included those with type 1 VWD with VW factor activity–ristocetin cofactor ratio ≤ 20% and unresponsive to desmopressin, patients with type 2 VWD not responsive to desmopressin and all subjects with type 2B and type 3 VWD. Entry criteria were strictly defined, as were therapy escalation parameters and clinical data collection. Results Eleven subjects completed the study. Six had type 2A, and five had type 3 VWD. Six patients presented with epistaxis, three with GI bleeding, and two with joint bleeding. Seven had dose escalation above the first level. Among the 10 subjects with evaluable bleeding log data, use of prophylaxis decreased the median annualized bleeding rate from 25 to 6.1 (95% confidence interval of the rate difference: −51.6 to −1.7), and the median annualized bleeding rate was even lower (4.0; 95% confidence interval: −57.5 to −5.3) when the subjects reached their final dosing level. Conclusion This is the first prospective study to demonstrate that prophylaxis with VW factor concentrates is highly effective in reducing mucosal and joint bleeding rates in clinically severe VWD.